Water Management for Rice in Tidal Lowland Reclamation Areas of South Sumatera, Indonesia - Momon Sodik Imanudin; Bakri Bakri; Satriaj Priatna; A Majid; Hengky Syaputra (Journal of Wetlands Environmental Management, 2023)
Tidal lowland reclamation aims to extend food agricultural area. Land clearing was done at Delta Telang II, Kabupaten Banyuasin District, South Sumatra I period of 1981-1982. Most area of Delta Telang II had land typology of B/C and almost half of it already been changed into palm oil plantation. Therefore, the field study had been conducted to determine the potentials and constraints for development of paddy field.  The research method was applied study and field experiment. Soil physical properties analyzed were texture, volume weight, and hydraulic conductivity.  Rice used in this study was Inpara 3 variety. The research results showed that soil physical properties was appropriate for development of paddy field rice. Controlling of water level in tertiary level by farmers was a key succeeds to provide water for crops. Model of water gate is flap gate type and it is operated dominantly as drainage during rice growth period and only functioned as supply when crops entering generative phase. Average rice production was 7.5 t ha-1. This condition was showed that using proper water management, balance fertilizer application, and adaptive rice variety resulted in successful rice crops cultivation at tidal lowland area and subsequently prevent land functional shifting.  Key words: Tidal lowland reclamation, water management, rice.